Innovations in Internationalisation at Home - Manning, Anthony (Cambridge Scholars Publisher, 2021)
This volume highlights new trends and projects in Internationalisation at Home (IaH) and internationalisation of the Higher Education curriculum in the UK and around the world. It brings together the contributions of academics and practitioners in the sector operating in different fields, from curriculum development to language teaching and academic support.